2007
DOI: 10.1111/j.1469-8137.2007.02301.x
|View full text |Cite
|
Sign up to set email alerts
|

Height convergence in response to neighbour growth: genotypic differences in the stoloniferous plant Potentilla reptans

Abstract: Summary Using a new experimental set up, the way in which height growth of stoloniferous plants is adjusted to that of their neighbours, as well as differences between genotypes in their ability to keep up with neighbour height growth were tested. Five Potentilla reptans genotypes inherently differing in petiole length were subjected to three experimental light gradients, involving light intensity and red : far‐red ratio. Each plant was placed in a vertically adjustable cylinder of green foil, and the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…Under natural conditions these costs associated with elongation can be compensated by the increased resource uptake after elongation has taken place (Huber & Wiggerman, 1997; Weijschede et al. , 2006, 2008b; Vermeulen et al. , 2008; Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Under natural conditions these costs associated with elongation can be compensated by the increased resource uptake after elongation has taken place (Huber & Wiggerman, 1997; Weijschede et al. , 2006, 2008b; Vermeulen et al. , 2008; Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved through either phenotypic manipulation or genetic transformation. An example is provided by studies that used these techniques to successfully test the supposed density dependence of fitness consequences of stem elongation (see Schmitt et al 1999; Vermeulen et al 2008). …”
Section: Validation Of Optimization Criteriamentioning
confidence: 99%
“…Maliakal et al (1999) working with I. capensis and Ballaré et al (1991) with Amaranthus quitensis both report that stimulation of height growth does not cause a reduction in root or leaf growth. On the other hand, Vermeulen et al (2008a) found through experimental manipulation of R:FR, an increase in petiole length and petiole mass for Potentilla reptans but decrease in root, stolon, and total biomass. They also report that petiole length can be limited by the productive capacity of plants.…”
Section: Plants As Competitorsmentioning
confidence: 91%